Random perturbation of the projected variable metric method for nonsmooth nonconvex optimization problems with linear constraints - El Mouatasim, Abdelkrim; Ellaia, Rachid; Souza de Cursi, Eduardo (Zielona Góra: Uniwersytet Zielonogórski)
We present a random perturbation of the projected variable metric method for solving linearly constrained nonsmooth (i.e., nondifferentiable) nonconvex optimization problems, and we establish the convergence to a global minimum for a locally Lipschitz continuous objective function which may be nondifferentiable on a countable set of points. Numerical results show the effectiveness of the proposed approach.
Keywords: global optimization; linear constraints; variable metric method; stochastic perturbation; nonsmooth optimization